A de novo variant in the ASPRV1 gene in a dog with ichthyosis - Bauer, Anina (PLoS Genet, 2017)
Ichthyoses are a heterogeneous group of inherited cornification disorders characterized by generalized dry skin, scaling and/or hyperkeratosis. Ichthyosis vulgaris is the most common form of ichthyosis in humans and caused by genetic variants in the FLG gene encoding filaggrin. Filaggrin is a key player in the formation of the stratum corneum, the uppermost layer of the epidermis and therefore crucial for barrier function. During terminal differentiation of keratinocytes, the precursor profilaggrin is cleaved by several proteases into filaggrin monomers and eventually processed into free amino acids contributing to the hydration of the cornified layer. We studied a German Shepherd dog with a novel form of ichthyosis. Comparing the genome sequence of the affected dog with 288 genomes from genetically diverse non-affected dogs we identified a private heterozygous variant in the ASPRV1 gene encoding “aspartic peptidase, retroviral-like 1”, which is also known as skin aspartic protease (SASPase). The variant was absent in both parents and therefore due to a de novo mutation event. It was a missense variant, c.1052T>C, affecting a conserved residue close to an autoprocessing cleavage site, p.(Leu351Pro). ASPRV1 encodes a retroviral-like protease involved in profilaggrin-to-filaggrin processing. By immunofluorescence staining we showed that the filaggrin expression pattern was altered in the affected dog. Thus, our findings provide strong evidence that the identified de novo variant is causative for the ichthyosis in the affected dog and that ASPRV1 plays an essential role in skin barrier formation. ASPRV1 is thus a novel candidate gene for unexplained human forms of ichthyoses.